PENERAPAN GAME BASED LEARNING EDUCAPLAY UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PADA PEMBELAJARAN IPAS SEKOLAH DASAR - Silvia Dwi Rahayu; Dian Permatasari Kusuma Dayu; Rosniwaty; Himmatul Khoiroh; Wiwik Moeljaningsih (STKIP Subang, 2024)
With the current teaching methods teachers use, it tends to make lessons boring because the atmosphere of the learning process is not interesting and students tend to find it difficult to focus on the learning process, as is the case at SDN Gading V Surabaya. Students tend to get bored and noisy during this lesson, so researchers are looking for alternatives to increase student activity in the learning process, namely with game-based learning education. This research aims to increase student activity at the elementary school level. The subjects of this research were class IV students at SDN Gading V Surabaya, totaling 15 boys and 16 girls. The method used is the Classroom Action Research (PTK) method using 2 learning cycles. Each cycle carries out planning, implementation, observation, and reflection activities. In-depth observation techniques using observation sheets regarding student activity, interviews, test questions in the form of descriptions, and field notes taken during learning. In this study, the results from cycle I was 48%, increasing to 31% in cycle II to 78%. Then the increase in learning activity in students was shown by the percentage increase in learning activity in the pre-cycle which was originally 32%, increasing in cycle I by 16% to 48% and increasing by 31% in cycle II to 79%. The average score for students' active learning results increased from cycle I, namely 76 to 87 in cycle II. Based on the research results, the application of Game-Based Learning Educaplay in science and science subjects can increase the learning activity of class IV students at SDN Gading V Surabaya.